The consequences of additional cognitive load on performing musicians. (July 2015) - Çorlu, Muzaffer; Muller, Chris; Desmet, Frank; Leman, Marc
When musicians play music, they seem to be fully concentrating and occupied with their performance. But what happens when concentration is affected, such as during examinations or concert performances? Our hypothesis was that the expressiveness of the music would be affected due to the fact that an additional cognitive load would occupy the cognitive resources that are needed for the timing and articulation of the musical action. To test this hypothesis, we asked experienced musicians to perform a musical piece with and without a secondary task (dual task condition). Jury judgements revealed that pieces performed under an additional cognitive load suffered a decrease in expressiveness. An analysis of the audio recordings revealed that for almost all performances, the durations of the pauses in between musical phrases during the performance in dual task conditions were significantly shorter than those performed without a secondary task, while the musical phrases themselves were not affected in their duration. We attribute this phenomenon to the fact that musicians can base the timing during playing on a (non-cognitive) corporeal reference, while during the pauses, this reference is lost. Insight into this effect may lead to educational practices that teach how to cope with additional load.